A GEOGRAPHICAL-POLITICAL ANALYSIS OF THE DETERMINANTS OF GOOD GOVERNANCE IN IRAQ: THE INTERNAL DETERMINANTS AS - Kelaiwy, Lateef Kamel (International Journal of Psychosocial Rehabilitation, 2018)
The state is the main actor in the implementation of good governance as it is concerned with setting the general policies through the formulation of laws and legislation and the development of appropriate mechanisms for their application. This is in addition to  its role in motivating the masses to popular participation in decision-making, maintaining security and respecting the principles of human rights, as well as freedom of the media and achieving Social justice and the protection of women’s rights. Besides that, it has a great role in providing housing, environmental protection and justice in the distribution of resources. The countries vary in the level of their application of good governance. This variation is due to internal and external factors that obstruct the path of the state and determine its behavior. Indeed, there is no evidence for that in Iraq, which was subjected to determinants both Internal and external distances kept it away from adopting the principles of good governance. Therefore, this paper comes to reveal the internal determinants that afflicted the state and undermined good governance in it, as well as providing effective solutions